Heart Failure in Women With Hypertensive Disorders of Pregnancy: Insights From the Cardiovascular Disease in Norway Project. Issue 5 (November 2020) - Honigberg, Michael C.; Riise, Hilde Kristin Refvik; Daltveit, Anne Kjersti; Tell, Grethe S.; Sulo, Gerhard; Igland, Jannicke; Klungsøyr, Kari; Scott, Nandita S.; Wood, Malissa J.; Natarajan, Pradeep; Rich-Edwards, Janet W.
Abstract : Hypertensive disorders of pregnancy (HDP) have been associated with heart failure (HF). It is unknown whether concurrent pregnancy complications (small-for-gestational-age or preterm delivery) or recurrent HDP modify HDP-associated HF risk. In this cohort study, we included Norwegian women with a first birth between 1980 and 2004. Follow-up occurred through 2009. Cox models examined gestational hypertension and preeclampsia in the first pregnancy as predictors of a composite of HF-related hospitalization or HF-related death, with assessment of effect modification by concurrent small-for-gestational-age or preterm delivery. Additional models were stratified by final parity (1 versus ≥2 births) and tested associations with recurrent HDP. Among 508 422 women, 565 experienced incident HF over a median 11.8 years of follow-up. After multivariable adjustment, gestational hypertension in the first birth was not significantly associated with HF (hazard ratio, 1.41 [95% CI, 0.84–2.35], P =0.19), whereas preeclampsia was associated with a hazard ratio of 2.00 (95% CI, 1.50–2.68, P <0.001). Among women with HDP, risks were not modified by concurrent small-for-gestational-age or preterm delivery ( P interaction =0.42). Largest hazards of HF were observed in women whose only lifetime birth was complicated by preeclampsia and women with recurrent preeclampsia. HF risks were similar after excluding women with coronary artery disease. In summary, women with preeclampsia, especially those with one lifetime birth and those with recurrent preeclampsia, experienced increased HF risk compared to women without HDP. Further research is needed to clarify causal mechanisms. Abstract : Supplemental Digital Content is available in the text.